Prediction and Analysis of Bending Fatigue Crack Growth Behavior of Spur Gear - Liu Xinbo; Zeng Xiaosong; Liu Yong (Jixie chuandong, 2016)
Based on the involute cylindrical gear as research object,the initial premise of the existence of cracks on the tooth root,the root of the fatigue crack growth characteristics and life are studied. The dynamics calculation of the gears meshing is equivalent to multiple engagement position static analysis,the stress intensity factors at different positions are obtained. According to the linear elastic fracture mechanics, the linear equivalent of crack growth is carried out,by using K criterion to analyze whether the crack extend. According to the Paris criterion to determine the amount of crack growth,using the maximum circumferential stress criterion to determine the crack growth angle,the stress intensity factor,crack growth path and fatigue life of the calculation cycle are obtained. By using high frequency test bench,the fatigue tests are carried out on the gear,the gear fatigue the expansion path is got,and comparing with the results of finite element calculation results.Finally,the influence of different initial crack size,position and load on fatigue crack growth and fatigue life is analyzed.